2014
DOI: 10.1097/qad.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Can high central nervous system penetrating antiretroviral regimens protect against the onset of HIV-associated neurocognitive disorders?

Abstract: Patients with higher CPE scores upon inclusion and at the end of follow-up were at lower risk of clinical worsening, suggesting that combination antiretroviral therapy with better CSF penetration could protect against cognitive deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 21 publications
0
31
2
Order By: Relevance
“…Our observations confirm this association, suggesting a significant cut-off of <308 cells/µL for onset of NCI. In contrast, for the CPE score, previous findings do not appear to support ours [39][43]. As described above, our results suggest that higher CPE scores may be associated with a higher probability of impairment.…”
Section: Discussioncontrasting
confidence: 99%
“…Our observations confirm this association, suggesting a significant cut-off of <308 cells/µL for onset of NCI. In contrast, for the CPE score, previous findings do not appear to support ours [39][43]. As described above, our results suggest that higher CPE scores may be associated with a higher probability of impairment.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a French cohort, a prospective neuropsychological analysis indicated that patients receiving treatments with a higher CPE score had a lower risk of clinical deterioration, suggesting that combination ART with better CPE could protect against cognitive deterioration [17].…”
Section: Discussionmentioning
confidence: 99%
“…In studies examining individuals with ART-controlled HIV viremia, HIV DNA in PBMCs correlated with regional brain atrophy highlighting the contribution of peripheral viral reservoirs to CNS pathology [168]. Even the modified HAART regimens that include drugs with better CNS penetration effectiveness (CPE) scores, termed neuro-HAART, have had limited success among patients [169-171]. Researchers have suggested various approaches to targeting latent CNS HIV reservoirs and sources of neuroinflammation such as cytokines, chemokines and oxidative stress that are in play inside the CNS and are refractory to antiretrovirals.…”
Section: Treatment Modalities For Handmentioning
confidence: 99%